An experimental study of iodine retention in Ag-zeolites at high humidity conditions - Lind, Terttaliisa; Espegren, Fredrik; Suckow, Detlef (Frontiers in Nuclear Engineering, 2025)
During severe accidents in nuclear power plants, filtered containment venting system is foreseen to be employed once the containment pressure increases above a pre-set value called venting pressure. Ag-zeolite filters are applied in filtered containment venting systems to retain iodine and organic iodides in the gas phase. In this work, the applicability of Ag-zeolites to not only retain gas phase iodine species, but to also catalyze hydrogen recombination has been experimentally investigated under challenging high humidity conditions. Tests were performed in the medium-scale facility using two Ag-zeolites, one of them designed to both retain gas phase iodine species and recombine hydrogen, the other one designed to only retain gas phase iodine species. Experiments studied the effect of residence time and the carrier gas mixture (steam, N2 or air) on the retention of organic iodine, represented in the tests by CH3I, and hydrogen recombination rate with the two Ag-zeolites. The experiments were carried out under the conditions expected in the containment during severe accidents, however, considering practical limitations. The effects of pressure and the presence of contaminant gases (CO, N2O) were investigated in additional tests not included in this study. The steam fraction in the tests varied between 32% and 90%, air fraction was 0%, 5% or 19%, and hydrogen content either 2.5% or 5%. Nitrogen made up the balance for the gas atmosphere. Gas residence time in the zeolite bed was either 100 m or 200 m. Both zeolites showed high retention of CH3I under all the gas atmospheres as long as the residence time in the reaction chamber was 200 m. CH3I retention was lower when the residence time was reduced to 100 m. Hydrogen recombination was more dependent on the gas atmosphere, as expected. The effect of the gas atmosphere on the hydrogen recombination and retention is discussed.